Risk of SARS-CoV-2 Infection Among People Living With HIV in Wuhan, China - Wu, Mengmeng; Ming, Fangzhao; Wu, Songjie; Liu, Yanbin; Zhang, Xiaoxia; Guo, Wei; Marley, Gifty; Tang, Weiming; Liang, Ke (Frontiers in Public Health, 2022)
Background: In the era of the COVID-19 pandemic, people living with HIV (PLWH) face more challenges. However, it is unclear if PLWH are more susceptible to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection than HIV-negative individuals. This study aimed to explore the prevalence of SARS-CoV-2 infection and associated risk factors among PLWH. Methods: From 1st to 30th May, 2020, we conducted a cross-sectional survey which enrolled 857 PLWH and 1048 HIV-negative individuals from the Wuchang district in Wuhan, China. Our data analysis compared the rate of SARS-CoV-2 infection among PLWH and HIV-negative participants, and the proportions of symptomatic patients and asymptomatic infectors between the two groups. We also assessed the risk factors associated with SARS-CoV-2 infection among PLWH. Results: Overall, 14/857 (1.6%) PLWH and 68/1048 (6.5%) HIV-negative participants were infected with SARS-CoV-2. Among SARS-CoV-2 infected PLWH participants, 6/14 (42.8%) were symptomatic patients, 4/14 (28.6%) were SARS-CoV-2 nucleic acid positive asymptomatic infectors, and 4/14 (28.6%) were serology positive asymptomatic infectors. Among infected HIV-negative participants, 5/68 (7.4%) patients were symptomatic and 63/68 (92.6%) were serology positive asymptomatic infectors. The rate of SARS-CoV-2 infection was lower among PLWH than in the HIV-negative group (1.96% vs. 5.74%, P=0.001) and the rate of morbidity among symptomatic patients was similar between the two groups (P=0.107). However, there were more serology positive asymptomatic infectors among infected HIV-negative participants than among infected PLWH (0.54% vs. 5.46%, P=0.001). Furthermore, being 50 years or older (aOR=4.50, 95% CI: 1.34-15.13, P=0.015) and having opportunistic infections (aOR=9.59, 95% CI: 1.54-59.92, P=0.016) were associated with an increased risk of SARS-CoV-2 infection among PLWH. Conclusions: PLWH have more varied forms of SARS-CoV-2 infection than the HIV-negative population and should therefore undertake routine screening to avoid late diagnosis. Also older age (≥50 years) and having opportunistic infections increases the risks of SARS-CoV-2 infection among PLWH.